2002
DOI: 10.1007/s00134-002-1416-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of procalcitonin and interleukin 6 in critically ill patients with suspected sepsis

Abstract: Admission and day 2 IL-6, and day 2 PCT, and day 2 D-dimer values differed significantly between hospital survivors and nonsurvivors among critically ill patients with suspected sepsis. However, in prediction of hospital mortality, only the discriminative power of day 2 PCT and IL-6 values, and APACHE II was reasonable as judged by AUC analysis (>0.75).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
1
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(125 citation statements)
references
References 40 publications
6
109
1
9
Order By: Relevance
“…In contrast, a decline in serum procalcitonin level was observed within 24 h of the start of appropriate treatment. 26 Earlier studies 27,28 in sepsis patients showed that serum procalcitonin levels at 24 h after hospital admission predicted mortality more accurately than those measured on hospital admission. In short, the procalcitonin levels measured at 24 h after hospital admission may have already reflected the patients' clinical course.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a decline in serum procalcitonin level was observed within 24 h of the start of appropriate treatment. 26 Earlier studies 27,28 in sepsis patients showed that serum procalcitonin levels at 24 h after hospital admission predicted mortality more accurately than those measured on hospital admission. In short, the procalcitonin levels measured at 24 h after hospital admission may have already reflected the patients' clinical course.…”
Section: Discussionmentioning
confidence: 99%
“…(16) Another study showed that serum PCT values measured in day 2 after hospital admission discriminated between survivors and non-survivor patients with sepsis. (17) Trying to correlate CRP serum values with sepsis mortality, Devran and his colleagues found out that when on the 3 rd day CRP value is > 100 mg/L, this is significantly correlated with mortality in severe sepsis, being a better mortality predictor than first day CRP value. They also showed that 3 rd day CRP value > 100 mg/L is comparable with a high SOFA score in predicting mortality.…”
Section: Discussionmentioning
confidence: 99%
“…White cell count and CRP were not found to be predictors of mortality in this study. 41 On the other hand, in another study 42 there was a significant difference in PCT values between survivors and non-survivors, but only the Acute Physiology and Chronic Health Evaluation (APACHE II) score and male gender were found to be independent predictors for death. In another recent study, CRP, SOFA score, age, and gender could predict mortality, but not PCT.…”
Section: Procalcitonin As a Prognostic Marker Of Bacterial Infectionsmentioning
confidence: 90%